The analysis of evolution of the State graduation exam in mathematics - Pekarskas, Vidmantas Povilas (Lietuvos matematikos rinkinys, 2012)
An overview on changes in the structure and topics of the State graduation exam in mathematics in the period from 1999 until 2012 is given in this paper. Topics frequently introduced in the contents of the exam and topics unpopular amongst the organizers of the exam are singled out. It is determined that more complex nonstandard problems have disappeared from the contents of the exam.